A MANBA mutation resulting in residual beta-mannosidase activity associated with severe leukoencephalopathy: a possible pseudodeficiency variant - Renard Dimitri; Garcés Violeta; Nieto Michèle; Labauge Pierre; Stensland Hilde; Sabourdy Frédérique; Castelnovo Giovanni; de Champfleur Nicolas; Levade Thierry (BMC, 2009)
Abstract Background β-Mannosidosis (OMIM 248510) is a rare inborn lysosomal storage disorder caused by the deficient activity of β-mannosidase, an enzyme encoded by a single gene (MANBA) located on chromosome 4q22-25. To date, only 20 cases of this autosomal recessive disorder have been described and 14 different MANBA mutations were incriminated in the disease. These are all null mutations or missense mutations that abolish β-mannosidase activity. In this study, we characterized the molecular defect of a new case of β-mannosidosis, presenting with a severe neurological disorder. Methods Genomic DNA was isolated from peripheral blood leukocytes of the patient to allow MANBA sequencing. The identified mutation was engineered by site-directed mutagenesis and the mutant protein was expressed through transient transfection in HEK293T cells. The β-mannosidase expression and activity were respectively assessed by Western blot and fluorometric assay in both leukocytes and HEK293T cells. Results A missense disease-associated mutation, c.1922G>A (p.Arg641His), was identified for which the patient was homozygous. In contrast to previously described missense mutations, this substitution does not totally abrogate the enzyme activity but led to a residual activity of about 7% in the patient's leukocytes, 11% in lymphoblasts and 14% in plasma. Expression studies in transfected cells also resulted in 7% residual activity. Conclusion Correlations between MANBA mutations, residual activity of β-mannosidase and the severity of the ensuing neurological disorder are discussed. Whether the c.1922G>A mutation is responsible for a yet undescribed pseudodeficiency of β-mannosidase is also discussed.